"So it's got three meanings dil dil:" Seductive ideophony and the sounds of Navajo poetry. (6th March 2017) - Webster, Anthony K.
Abstract: This article engages questions about translation, phonological iconicity, and seductive ideophony. I begin by discussing the work of Paul Friedrich as it relates to questions of linguistic relativity and poetics and the qualities of music and myth that constitute poetry. I then present a poem written in Navajo by Rex Lee Jim and four translations of the poem. Three are from Navajo consultants and one of those translations will be, from a certain perspective, rather surprising. Namely, why does one consultant translate this poem as if it is composed of ideophones? The fourth translation is mine. I then work through the morphology of the poem in Navajo, saying something more about the translators and the process of translation. I then provide a transcript of a conversation I had with Blackhorse Mitchell about this poem. I use this to take up questions of phonological iconicity (punning) and the seductive quality of ideophony (the pole of music). I also place this poem within a context of the stick game in Navajo philosophy (the pole of myth). This leads, in the conclusion, to reflections about linguistic relativity, misunderstandings, sound, and poetics. Résumé: Cet article soulève des questions sur la traduction, sur l'iconicité phonologique et sur la séduction de l'idéophonie. Je discute d'abord du travail de Paul Friedrich (1979, 1986 sur les questions de relativité linguistique et de poétique, et les qualités de la musique et du mythe qui constituent la poésie. Je présente ensuite un poème écrit en Navajo par Rex Lee Jim, et quatre traductions du poème, dont trois faites par des consultants navajo. L'une de ces trois sera, d'un certain point de vue, assez surprenante : pourquoi le consultant a-t-il traduit le poème comme s'il était composé d'idéophones? La quatrième traduction est de moi. J'analyse la morphologie du poème en Navajo, avec des commentaires au sujet des traducteurs et du processus de traduction. Je fournis ensuite la transcription d'une conversation que j'ai eue au sujet de ce poème avec Blackhorse Mitchell. Cette conversation me permet d'aborder des questions d'iconicité phonologique (calembours) et de la séduction qu'exerce l'idéophonie (le pôle de la musique). Je situe le poème dans le contexte du jeu de bâton dans la philosophie navajo (le pôle du mythe). Cela mène, en conclusion, à des réflexions sur la relativité linguistique, les malentendus, le son et la poétique.